if the quadratic formula is used to find the roots of the equation x^2-6x-19=0, what is the correct roots

Answers

Answer 1
Answer: x^(2) -6x-19=0 \n  \ndiscriminant= b^(2)-4ac=> \n 36-(-76)=76+36=112 \n  \n -b- √(disc.)/2a=>6- √(112)/2 \n =>6- 4√(7)/2 \n  =3- 2√(7)  \n  \n -b +√(disc)/2a=6+4 √(7) /2 \n =3+ 2√(7)  \n  \n Solution\: set:(3-   2√(7)  ,3+ 2√(7) ) \n  \n \framebox[1.1\width]{Good Luck!!} \par
Answer 2
Answer: x^2-6x-19=0\nx^2-6x+9-28=0\n(x-3)^2=28\nx-3=√(28) \vee x-3=-√(28)\nx=3+2\sqrt7 \vee x=3-2\sqrt7

Related Questions

Tian makes his own pizza dough. he uses 2 packages of yeast for every 5 cups of flour. if he needs 15 cups of flour to make enough pizza for his family, how many packages of yeast does he need?
X + y = 155x - y = 9Elimination method (4, ? )what number is the ?​
What is the answer..........
Lynn street, Allen street, and route 11 form the boundaries of a triangular forest, as shown in the map below.
Find three points and then graph: y 3/4x-1

The ratio of Sam's age to Hank's age is 5 to 3. If the sum of their ages is 24, how old is Hank?

Answers

S-Sam's\ age\nH-Hank's\ age\n\n \left\{\begin{array}{ccc}(S)/(H)=(5)/(3)\nS+H=24&\to S=24-H\end{array}\right\n\nsubstitute\ S=24-H\ to\ (S)/(H)=(5)/(3)\n\n(24-H)/(H)=(5)/(3)\n\ncross\ multiply\n\n5H=3(24-H)\n5H=72-3H\n5H+3H=72\n8H=72\ \ \ /:8\nH=9\n\nAnswer:Hank\ is\ 9\ years\ old.

Which variable is most important to the following problem?A tentmaker has 60,000 tents in stock. The Army decides to order 350 tents
for each of its 200 brigades. Will the tentmaker have enough tents in stock?
O A. the price of one tent
O B. the number of tents the Army orders
C. the size of each tent

Answers

Answer:

B.) the number of tents the army orders

Step-by-step explanation:

The word problem does not speak of any prices or tent sizes so it cant be A or C

Answer:

its B

Step-by-step explanation:

Select the correct answer. The sum of two numbers is -18. If the first number is 10, which equation represents this situation, and what is the second number? A. The equation that represents this situation is 10 − x = -18. The second number is 28. B. The equation that represents this situation is 10 + x = -18. The second number is -28. C. The equation that represents this situation is x − 10 = -18. The second number is -8. D. The equation that represents this situation is -10 + x = -18. The second number is -8.

Answers

Answer:-28

Step-by-step explanation:

Let A is the second number

the first number is 10.

The total is -18

=> 10 + A =-18 <=> A=-18-10=-28

The product of a + 3 and –2a2 + 15a + 6 is –2a3 + xa2 + 51a + 18. What is the value of x?A=3
B=9
C=12
D=15

Answers

(A+3) x ( -2A2+15A+6) = (-2A3+XA2+51A+18)
(3+3) x ( -2*3*2+15*3+6) = (-2*3*3+X *3*2+51*3+18)
(6) x (-2*3*2=-12 + 15*3=45 +6 = 51
(6) x (-12 +51=39)
6 x 39 =( -2*3*3= -18)+ x *3*2+(51*3+18=171)
6 x 39 -18 + x*3*2+ 171
6 x 39 =234
234 -171=63
-18 + 5x=63
X = 13.5

What value of x is in the solution set of 9(2x + 1) < 9x – 18?

Answers

To solve these kinds of problems, it is necessary to isolate x:

9(2x + 1) < 9x - 18

Distribute 9:
18x + 9 
< 9x - 18

Subtracting 9 from both sides of the equation:
18x + 9 - 9 
< 9x - 18 - 9
18x 
< 9x - 27

Subtracting 9x from both sides of the equation:
18x - 9x 
< 9x - 27 - 9x
9x 
< -27

< -3

Therefore, values of x 
< -3 will satisfy the given equation.

Answer:

x ∠ -3

Step-by-step explanation:

To solve this inequalities, we have to follow the steps below

open the bracket

collect like term

subtract and then divide both-side so that we can be left with just the variable

9(2x +1) < 9x - 18

opening the bracket, equation becomes;

18x + 9  < 9x - 18

collect like terms, numbers with x variables on the left hand side and number standing alone on the right hand side of the inequality

18x - 9x < -18-9  

9x <  -27

Divide both-side of the equation by 9

9x/9 < -27/9

Help please and thank you!

Answers

Answer:

  25.  (x, y) = (5, 11)

  26.  (x, y) = (-1, 1)

Step-by-step explanation:

Both equations are of the form y=( ), so you can set the expressions for y equal to each other. Or, you can subtract the equation with the smaller y-coefficient from the other one.

25.

  x +6 = y = 2x +1 . . . . . equate expressions for y

  5 = x . . . . . . . . . . . subtract x+1

  y = 5+6 = 11 . . . . . using the first equation to find y

  (x, y) = (5, 11)

__

26.

  (y) -(y) = (3x +4) -(x+2) . . . . subtract the first equation from the second

  0 = 2x +2 . . . . . . . . . . . . . . simplify

  0 = x + 1 . . . . . . . . . . . . . . . . divide by the x-coefficient

  x = -1 . . . . . . . . . . . . . . subtract the constant

  y = -1 +2 = 1 . . . . . . . . . use the first equation to find y

  (x, y) = (-1, 1)

_____

Of course, when we say "subtract ..." or "divide ..." we mean that you should do the same operation to both sides of the equation. That way the equal sign remains valid. You can always use an expression or variable in place of its equal (this is the substitution property of equality).

The expression (x+1) that we subtract in problem 25 is the smaller x-term plus the constant on the opposite side of the equal sign. That way, we eliminate both the unwanted x-term and the unwanted constant. You can do these operations one at a time (and you were probably taught to do it that way). That is, subtract x; subtract 1.

For 26, the method of solution that puts both the variable and the constant on the same side of the equation and 0 on the other side has certain advantages. Subtracting one side of the equation from both sides (to make an expression equal to zero) will always work, regardless of the expressions involved. After simplification, you can divide by the coefficient of the variable to get the form x+constant=0, and the answer is always x = -constant. These simple instructions require no judgment. You may find it easier to choose to subtract the side with the smaller coefficient, so the result has a positive coefficient. That's not necessary, but it can reduce anxiety and errors.